The Six-Minute Stepper Test Is Valid to Evaluate Functional Capacity in Hospitalized Patients With Exacerbated COPD - Ribeiro, Diego Britto; Terrazas, Aline Carleto; Yamaguti, Wellington Pereira (Frontiers in Physiology, 2022)
BACKGROUND: The six-minute stepper test (6MST) is a self-paced test considered a valid tool to assess functional capacity in stable COPD patients. However, a high floor effect, the situation in which a large proportion of participants who reach the minimum score when using the measurement instrument, might compromise the test validity in the hospital setting. Therefore, this study aimed at verifying the concurrent validity of 6MST in hospitalized patients with acute exacerbation of COPD (AECOPD). METHODS: A cross-sectional study was conducted in a tertiary hospital. Patients who were hospitalized due to AECOPD were considered for inclusion. On the first day, when patients reached minimum clinical criteria considered as the use of non-invasive ventilation less than 2 hours for 6 hours/period, dyspnea at rest less than 7 (very severe) on the modified Borg scale, respiratory rate less than 25 breaths per minute, oxygen pulse saturation greater than 88% (considering use of supplemental oxygen) and absence of paradoxical breathing pattern, they underwent a lung function evaluation and answered three questionnaires: Chronic Respiratory Questionnaire, Modified Medical Research Council Dyspnea Scale, and COPD Assessment Test (CAT). Then, on two consecutive days, patients performed 6MST or six-minute walk test (6MWT), in random order. Each test was performed twice and the best performance was recorded. The patient's severity was classified according to the BODE index. Inspiratory capacity measurements were performed before and after each test. RESULTS: Sixteen patients (69.4±11.4 years) with a mean FEV₁ 49.4±9.9% predicted were included (9 females). There was a strong correlation of the performance in 6MST (number of cycles) with 6MWT (distance walked in meters) in absolute values (r=0.87, p<0.001) as well as with the percentage of predicted normal 6MWT (r=0.86, p<0.001). There was a strong correlation of the performance in 6MST with the dynamic hyperinflation (r=0.72, p=0.002) and a moderate correlation of 6MST with the percentage of reduction of inspiratory capacity (r=0.68, p=0.004). We also identified that 6MST showed moderate negative correlations with CAT (r=-0.62, p=0.01) and BODE index (r=-0.59, p=0.01). CONCLUSION: It could be concluded that 6MST is valid for the evaluation of functional capacity in hospitalized patients with (AECOPD).